WASTE COPPER USAGE FOR PLANT FUNGICIDE PRODUCTION - Mustafa Burgić; Amir Fazlić; Mirela Burgić-Salihović (Journal of Engineering & Processing Management, 2013)
Copper Oxyl Chloride 3Cu (OH)2∙CuCl2 is dual salt of copper, chlorine, oxygen and water. It is light green salt without smell. In water and organic solutions it is insoluble while it is easily solluble in acids. It is solluble in ammonia thus building complex units. It is more instable product since it is soluted after longer exposure to air and moist. Most common use is for plant protection (it can be used as dust, oil or water suspension). There are various ways and patents to produce it. These technologies are mainly similar but each manufacturer starts from different base: copper or its salts, chlorides of alkaly metals oxidating with air exposure.
Keywords: cooper oxyl chloride; salt; organic solutions; alkaly metals